The Impact of TMT Advice Seeking Behaviour on Dynamic Service Innovation Capabilities: Evidence from the Service Sector in Sri Lanka - Kariyapperuma, Seshika Kithmini (Technium Social Sciences Journal, 2026)
This study investigates how Top Management Team (TMT) advice-seeking behaviors—both external and internal—shape the development of Dynamic Service Innovation Capabilities (DSIC). Although the literature has long emphasized executive decision-making, the specific consultative mechanisms that trigger DSIC remain underexplored. Using a quantitative methodology, data were collected via a standardized questionnaire from a sample of 260 TMT members across six diverse service sectors. The conceptual model was tested using Structural Equation Modeling (SEM) in AMOS. The results confirm that both TMT external and internal advice-seeking behaviors significantly and positively affect DSIC, supporting both research hypotheses. Specifically, external advice-seeking behaviour serves as a critical debiasing mechanism that enables TMTs to overcome path dependence and anticipate emerging market shifts. Simultaneously, internal advice-seeking fosters a climate of psychological safety and trust, catalyzing the conceptualization of new services and bridging the implementation gap through functional expertise. These findings contribute to the dynamic capabilities perspective by highlighting advice-seeking as a dual engine for organizational agility. In practice, the study suggests that service-sector leaders should adopt a “consultative-orchestration” model, formalizing external knowledge loops and internal feedback systems to develop dynamic service innovation capabilities that continuously bring innovations. Keywords. TMT Advice Seeking Behaviour, Dynamic Service Innovation Capabilities, Service Innovation